Effect of grading and grain size on the friction characteristics of a sand/geotextile inteface - Kalumba, Denis (Department of Civil Engineering, 2020)
Geofabrics are incorporated in geotechnical engineering structures for various reasons and functions. This study addresses the reinforcement function whereby geotextiles are utilised as reinforcing elements in reinforced slopes and fills. It particularly focuses on the soil/geotextile interface behaviour. Geotextile reinforcements transfer a majority of the shear stress from the soil to the reinforcement and vice versa by friction. This interfacing ability manifested by the soil/geotextile frictional contact is very important in the performance of reinforced soil structures, and depends on the physical characteristics of the backfill as well as the geotextile. In this investigation, the interaction behaviour of geotextiles with sand is evaluated by conducting extensive laboratory interface tests both in direct shear and pull-out. A comprehensive test program was established to include a needle punched non-woven geotextile interacting with sands of different grading, grain size distributions and grain shapes namely; Cape Flats, Klipheuwel and Munich sands. The respective responses were primarily presented in terms of shear stress/horizontal displacement and pUll-out resistance/front displacement relationships; showing the frictional performance of the geotextile in these sands of different physical characteristics. Interface shear strength in both test methods was determined using Mohr-Coulomb's law. The ensuing shear strength values were compared with each other and with the direct shear strengths of the respective sands used in this investigation Specific emphasis and detailed analyses went into the pull-out experiments in which local displacements of the geotextile specimens were measured as the test progressed. The measurements enabled the study of the stretching characteristics of the geofabric in the different sands. Applying an extrapolation procedure to approximate the constantly changing deformation modulus of the geotextile as it stretched in the respective sands, allowed the back-prediction of the pull-out force/displacement relationship, and thus enabled the study of skin friction distribution along the geotextile specimen during pull-out. The effect of the grading and grain size on the development of the interface shear stress, the peak values, and the type of interface failure could be demonstrated. The analysis of the skin friction along the geotextile specimen led to the development of a generalised shear stress distribution graph which, if validated in further research, may be adopted in practical design situations. In a design example, it was shown that the assumption of interface shear parameters based on direct shear tests provides too optimistic a factor of safety. This study recommends the use of interface shear parameters derived from pull-out tests. The in-depth analysis of the tests in a variety of sands showed clearly that the shear stress is not uniformly distributed over the embedment length of the reinforcement. This skin friction drops dramatically from a peak value near the loaded end to zero at the free end in all investigated confinements.